An Evaluation of Border Management Reforms in a Technical Agency - Fernandes, Ana M. (World Bank, Washington, DC, 2017)
Impact evaluations of trade facilitation reforms have almost exclusively focused on reforms by data-rich customs agencies. Other "technical" agencies also intervene in the logistics of international trade, and do so in ways that can cause significant interruptions in the flow of the imported products they oversee. This paper is the first to evaluate a reform by a technical agency, namely, the agency responsible for food safety and animal health in the former Yugoslav Republic of Macedonia. The data environment is much more challenging than in customs, but enables the investigation of novel questions. The study finds that on-the-ground practices regarding sampling of import shipments departed substantially from those planned in the reform. It finds little evidence that the reform was successful in its attempt to improve the targeting of risky shipments. There is limited evidence that the reform increased trade flows, but circumstances make it difficult to establish a strong causal link to the specific reform studied.